Characterisation and Mechanical Modelling of Polyacrylonitrile-Based Nanocomposite Membranes Reinforced with Silica Nanoparticles - Acarer, Seren; Pir, Inci; Tufekci, Mertol; Erkoc, Tugba; Oztekin, Vehbi; Dikicioglu, Can; Demirkol, Guler Turkoglu; Durak, Sevgi Gunes; Ozcoban, Mehmet Sukru; Coban, Tuba Yelda Temelli; Cavus, Selva; Tufekci, Nese (MDPI, 2022)
In this study, neat polyacrylonitrile (PAN) and fumed silica (FS)-doped PAN membranes (0.1, 0.5 and 1 wt% doped PAN/FS) are prepared using the phase inversion method and are characterised extensively. According to the Fourier Transform Infrared (FTIR) spectroscopy analysis, the addition of FS to the neat PAN membrane and the added amount changed the stresses in the membrane structure. The Scanning Electron Microscope (SEM) results show that the addition of FS increased the porosity of the membrane. The water content of all fabricated membranes varied between 50% and 88.8%, their porosity ranged between 62.1% and 90%, and the average pore size ranged between 20.1 and 21.8 nm. While the neat PAN membrane's pure water flux is 299.8 L/m(2) h, it increased by 26% with the addition of 0.5 wt% FS. Furthermore, thermal gravimetric analysis (TGA) and differential thermal analysis (DTA) techniques are used to investigate the membranes' thermal properties. Finally, the mechanical characterisation of manufactured membranes is performed experimentally with tensile testing under dry and wet conditions. To be able to provide further explanation to the explored mechanics of the membranes, numerical methods, namely the finite element method and Mori-Tanaka mean-field homogenisation are performed. The mechanical characterisation results show that FS reinforcement increases the membrane rigidity and wet membranes exhibit more compliant behaviour compared to dry membranes.
Keywords: nanocomposite membrane; polyacrylonitrile; fumed silica; membrane characterisation; mechanical modelling; WASTE-WATER TREATMENT; PERFORMANCE EVALUATION; STRENGTH; MATRIX; ENERGY; OXIDE; Chemistry; Science & Technology - Other Topics; Materials Science; Physics